Lattice structure design parameters optimization for the structural integrity of passive vibration isolator - Syafwan Azmi, Muhamad; Ismail, Rainah; Fadzli Bin Abdollah, Mohd (Manufacturing Technology Journal, 2022)
Passive vibration isolator with lower natural frequency has always been a challenge due to structural integrity issues. This study presents the use of RSM statistical tool to analyze and optimize the mechan-ical responses of BCC lattice structure for structural integrity in a passive vibration isolator application. The optimization was done to obtain low stiffness for low natural frequency but high yield stress for optimum load-bearing capability with unit cell size and strut diameter design parameters tweak. From the results, the significance and contribution of each design parameter on each mechanical response through compression test can be understood. Results indicated changes in strut diameter produced lin-ear growth while changes in the unit cell size produced inverse exponential responses. From optimiza-tion, a combination of 3.9 mm strut diameter with 10 mm unit cell size produced the optimum result. Therefore, it was demonstrated that RSM can provide statistical importance and contribution between input factors and their influence on each mechanical response with minimal test and cost.
Keywords: Lattice structure; Design parameter; Optimization; Structural integrity; Vibration isolator